Medical Assistance in Dying (MAiD): Human and Humanity in the Study of Fiqh Maqashid - Kutbuddin Aibak (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2023)
This study aimed to formulate the construction of fiqh maqashid as a standardization of the concept of humanity in Medical Assistance in Dying (MAiD). This study contributes to actualizing fiqh maqashid as a standardization of values in solving humanitarian problems. This is based on the phenomenon of MAiD, which is considered controversial in the eyes of social religion and state law as in the concept of Islamic law (fiqh), which sees that the protection and realization of human existence and humanity are essential values in the study of Islamic law (fiqh). This argumentation must be elaborated in depth regarding interests and benefit elements in the MAiD phenomenon. The stages of the realization of benefits in the context of the approach to Islamic law (fiqh) are one of the representations and forms of elasticity in the study of the objectives of Islamic law (maqashid al-sharia). The relevance of maqashid al-sharia studies as a form of maqashid fiqh approach is considered to carry urgency in determining aspects of benefit in the MAiD phenomenon and representing maqashid fiqh in realizing human protection and humanity. This study uses literature research with data from various phenomena and regulations on MAiD, which are presented descriptively and then critically analyzed through the fiqh maqashid approach. This study found that the realization of the MAiD program through euthanasia has implications for the non-realization of the essential values of maqashid al-sharia in fiqh maqashid. This study confirms that fiqh maqashid has an orientation towards solving human problems based on humanity